A statistical approach to identify candidate cues for nestmate recognition - van Zweden, Jelle S.; Pontieri, Luigi; Pedersen, Jes S. (Frontiers in Ecology and Evolution, 2014)
The ability of social insects to discriminate nestmates (NMs) from non-nestmates (nNMs) is mainly achieved through chemical communication. To ultimately understand this recognition and its decision rules, identification of the recognition cues is essential. Although recognition cues are most likely cuticular hydrocarbons (CHCs), identifying the exact cues for specific species has remained a daunting task, partly due to the sheer number of odor compounds. Perhaps unsurprisingly, one of the few species where the recognition cues have been identified, Formica exsecta, has only around ten major hydrocarbons on its cuticle. In this study we use previous results of this species to search for nestmate recognition cues (NMR cues) in two other species of ants, Camponotus aethiops, and Monomorium pharaonis. Employing chemical distances and observed aggression between colonies, we first ask which type of data normalization, centroid, and distance calculation is most diagnostic to discriminate between NMR cues and other compounds. We find that using a “global centroid” instead of a “colony centroid” significantly improves the analysis. One reason may be that this new approach, unlike previous ones, provides a biologically meaningful way to quantify the chemical distances between NMs, allowing for within-colony variation in recognition cues. Next, we ask which subset of hydrocarbons most likely represents the cues that the ants use for nestmate recognition, which shows less clear results for C. aethiops and M. pharaonis than for F. exsecta, possibly due to less than ideal datasets. Nonetheless, some compound sets performed better than others, showing that this approach can be used to identify candidate compounds to be tested in bio-assays, and eventually crack the sophisticated code that governs nestmate recognition.